SARS‐CoV‐2 receptor ACE2 and TMPRSS2 are primarily expressed in bronchial transient secretory cells - Lukassen, Soeren; Chua, Robert Lorenz; Trefzer, Timo; Kahn, Nicolas C; Schneider, Marc A; Muley, Thomas; Winter, Hauke; Meister, Michael; Veith, Carmen; Boots, Agnes W; Hennig, Bianca P; Kreuter, Michael; et al. (The EMBO journal, 2020)
The SARS‐CoV‐2 pandemic affecting the human respiratory system severely challenges public health and urgently demands for increasing our understanding of COVID‐19 pathogenesis, especially host factors facilitating virus infection and replication. SARS‐CoV‐2 was reported to enter cells via binding to ACE2, followed by its priming by TMPRSS2. Here, we investigate ACE2 and TMPRSS2 expression levels and their distribution across cell types in lung tissue (twelve donors, 39,778 cells) and in cells derived from subsegmental bronchial branches (four donors, 17,521 cells) by single nuclei and single cell RNA sequencing, respectively. While TMPRSS2 is strongly expressed in both tissues, in the subsegmental bronchial branches ACE2 is predominantly expressed in a transient secretory cell type. Interestingly, these transiently differentiating cells show an enrichment for pathways related to RHO GTPase function and viral processes suggesting increased vulnerability for SARS‐CoV‐2 infection. Our data provide a rich resource for future investigations of COVID‐19 infection and pathogenesis. Synopsis Coronavirus entry requires its binding to host cell receptor ACE2 and subsequent priming by TMPRSS2. Using unpublished single‐cell data of the human lung and bronchia, this study reveals expression of potential SARS‐CoV‐2 cofactors ACE2 , TMPRSS2 and FURIN primarily in bronchial cells transitioning from secretory to ciliated identity. Single‐cell dataset comprising 57,229 cells from the lung and subsegmental bronchial branches of 16 human donors was used for studying potential SARS‐CoV‐2 relevant host factors. In the bronchial epithelium, ACE2 is most strongly expressed in cells transient secretory cells. A subset of ACE2 + cells co‐expresses the proteases TMPRSS2 and/or FURIN Trends towards age‐ and sex‐dependent changes in ACE2 mRNA levels were observed. Graphical Abstract A single‐cell RNA‐seq resource identifies expression of coronavirus entry‐linked host cofactors ACE2 , TMPRSS2 and FURIN primarily in bronchial cells in cells transitioning from secretory to ciliated identity.